2013
DOI: 10.1002/cctc.201300801
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Conversion of Carbon Dioxide, Ethylene Oxide, and Amines to 3‐Aryl‐2‐oxazolidinones Catalyzed with Binary Ionic Liquids

Abstract: An effective one‐pot method for the conversion of carbon dioxide, ethylene oxide, and amines to 3‐aryl‐2‐oxazolidinones has been developed. This one‐pot method consists of two parallel reactions and a subsequent cascade reaction between the two products of the corresponding parallel reactions. Notably, the binary ionic liquids of 1‐butyl‐3‐methyl‐imidazolium bromide and 1‐butyl‐3‐methyl‐imidazolium acetate demonstrate a synergistic catalytic effect on this new strategy. 1‐Butyl‐3‐methyl‐imidazolium bromide is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 38 publications
4
60
0
1
Order By: Relevance
“…Gao et al. reported a three‐component synthesis of oxazolidinones from CO 2 , ethylene oxide, and amines catalyzed by binary ionic liquids (Scheme ) . This method, however, requires high CO 2 pressures (25 bar; 1 bar=0.1 MPa) and high temperatures (140 °C).…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Gao et al. reported a three‐component synthesis of oxazolidinones from CO 2 , ethylene oxide, and amines catalyzed by binary ionic liquids (Scheme ) . This method, however, requires high CO 2 pressures (25 bar; 1 bar=0.1 MPa) and high temperatures (140 °C).…”
Section: Methodssupporting
confidence: 69%
“…The reactor was pressurized to 10 bar with CO 2 and heated at 95 °C for 9 h. Upon completion of the reaction, the mixture was cooled to room temperature, and the pure product was isolated by column chromatography (EtOAc/petroleum ether 1:30). The structure was confirmed by comparison with literature data …”
Section: Methodsmentioning
confidence: 99%
“…It is clear that the C-2 proton of imidazolium ring shifted step by step upon addition of DEC due to its interaction with carbonyl group of DEC. Similar results were reported by us and others [24][25]41]. On the addition of 10 eq.…”
Section: Reaction Mechanism Studiessupporting
confidence: 91%
“…In the course of our studies on the utilization of ionic liquids as catalysts, we reported approaches for the synthesis of 3-aryl-2-oxazolidinones via reaction of cyclic carbonates with aromatic amines, and the straightforward conversion of CO 2 using ethylene oxide and aromatic amines in the presence of catalytic amount of ionic liquids [23][24][25][26]. Although these approaches are regarded as green, they still suffer from relative long reaction time, high reaction temperature or large amount of catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst proved to be highly efficient for the coupling reaction between aziridines and CO 2 under reasonable reaction conditions (100 °C, p(CO 2 ) = 80 bar) without the utilization of any additive or cosolvents making it a rather green process. ILbased systems have also been reported in this same context and proven to be attractive catalyst systems though relatively high reaction temperatures are generally warranted to achieve acceptable turnover rates [101,104,105]. This selective behavior was also noted for most of the other investigated substrates with regioselectivities in the range 86-99%.…”
Section: Figure 11mentioning
confidence: 63%